Food consumption of Chrysoperla externa in different developmental phases of Dysmicoccus brevipes, under laboratory conditions - Gonçalves-Gervásio, Rita de Cássia Rodrigues; Santa-Cecília, Lenira Viana Costa (Pesquisa Agropecuaria Brasileira, 2001)
The food consumption and preference of larvae of Chrysoperla externa Hagen, 1861 (Neuroptera: Chrysopidae) larval were studied in laboratory under 25±2oC, 70±10% RH and 12 hours photophase, utilizing the pineapple mealybug (Dysmicoccus brevipes Cockerell, 1893, Hemiptera: Pseudococcidae) as a prey. The results showed that the predator's larval phases consumed on average of 70, 50 and 15,8 mealybugs of the first, second and third instar, respectively, and 10 adult females amounting to 145,8 individuals. It was noticed that 51% of the total number of mealybugs were consumed during the predator third instar. The high number of mealybugs consumed shows that C. externa presents a potential to be utilized in biological control of the mealybug D. brevipes.